Extracorporeal membrane oxygenation support in oncological thoracic surgery - Mangiameli, Giuseppe; Testori, Alberto; Cioffi, Ugo; Alloisio, Marco; Cariboni, Umberto (Frontiers in Oncology, 2022)
Intraoperative extracorporeal lung support (ECLS) during thoracic surgical procedures is a modern concept that is gaining increasing acceptance. Firstly, introduced for lung transplantation, this technique is now increasingly adopted also in oncological thoracic surgery. In this review we focus on the cutting-edge application of extracorporeal membrane oxygenation (ECMO) in oncological thoracic surgery. Therefore, we report the most common surgical procedures that in oncological thoracic surgery can benefit from the use of ECMO. They will be classified and discussed according to the aim of ECMO application. In particular, the use of ECMO is usually limited to certain lung surgery procedures that can be resumed in procedures in which an adequate ventilation is not possible such as in single lung patients; procedures where conventional ventilation can cause collision with the surgical field such as tracheal or carinal surgery and conventional procedures requiring both ventilators and haemodynamic support. So far, all available evidence comes from centers with extensive experience in ECMO and major thoracic resections